A Perspective on Withania somnifera Modulating Antitumor Immunity in Targeting Prostate Cancer - Seema Dubey; Manohar Singh; Ariel Nelson; Dev Karan (Journal of Immunology Research)
Medicinal plants serve as a lead source of bioactive compounds and have been an integral part of day-to-day life in treating various disease conditions since ancient times. Withaferin A (WFA), a bioactive ingredient of Withania somnifera, has been used for health and medicinal purposes for its adaptogenic, anti-inflammatory, and anticancer properties long before the published literature came into existence. Nearly 25% of pharmaceutical drugs are derived from medicinal plants, classified as dietary supplements. The bioactive compounds in these supplements may serve as chemotherapeutic substances competent to inhibit or reverse the process of carcinogenesis. The role of WFA is appreciated to polarize tumor-suppressive Th1-type immune response inducing natural killer cell activity and may provide an opportunity to manipulate the tumor microenvironment at an early stage to inhibit tumor progression. This article signifies the cumulative information about the role of WFA in modulating antitumor immunity and its potential in targeting prostate cancer.